Socialization of the Negative Impact of Online Games among Students in Arahan Lor Village, Arahan District, Indramayu Regency - Ulifah Sarih (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This Community Service (PKM) activity was conducted in response to the high interest and tendency of elementary school students in Arahan Lor Village to play online games, which have the potential to negatively impact cognitive development, behavior, and learning motivation. The main objective of this program was to increase students' knowledge and awareness (the primary target was students of SDN 2 Arahan Lor) regarding the dangers of online game addiction. The implementation method used was interactive socialization and counseling, involving comprehensive explanations of playing time limits, identifying signs of addiction, and the detrimental impacts on academic achievement and mental health. The results of the activity showed a positive increase in students' understanding. The success of this program underscores the importance of the active role of the community and schools in providing digital education and ongoing supervision. This program is recommended as a preventative measure to create a conducive learning environment, support optimal student development, and protect them from the risks of gadget addiction.